Biocomposting process for utilization agro-industrial wastes - A. N, Kabbashi; Z. A, MD.; Othan, Ahmadi (2006)
Biological treatment has played prominent roles in bioremediation of wastes and contaminants. Composting is one of the biological process that has been considered to be one of the most suitable ways of converting organic wastes into products that are beneficial for plant growth. The study of the bio-composting process by solid-state bioconversion utilizing palm oil mill effluent (POME) and empty fruit bunch (EFB) were studied in lab scale. From the study it is found that horizontal rotary drum bioreactor was the most suitable to run this study. In this project, four filamentous fungi were used; (i) Phanerochaete chrysosporium. (ii) Trichoderma harzianum. (iii) Aspergillus niger. (iv) Penicillium sp. The bioconversion of lignocellulosic materials by evaluating the C/N ratio and other parameters using horizontal rotary drum bioreactor were studied. The good and mature of the compost is reflected by C/N ratio, germination index and glucosamine assay. The result showed that the C/N ratio drop from days 10 onwards and in the range of 25 to 30. The germination indexes of 50 to 70% indicate that the compost produce was a phyto toxic-free product and merely achieved as mature compost. The composting period required to complete this process was two months. Thus, this study developed an effective and feasible composting technique of POME and EFB using horizontal rotary drum bioreactor by solid state bioconversion process.